Participatory family workshops in psychosocial health and illness research: experiences from Danish health promotion projects. (22nd February 2022) - Grabowski, Dan; Pals, Regitze Anne Saurbrey; Hoeeg, Didde; Ingersgaard, Marianne Vie; DeCosta, Patricia; Jespersen, Louise Norman
Summary: Family involvement in health and illness research is a complex matter, often characterized by unclear structural relations and contrasting needs and expectations within the family. As the family is a setting in which health and illness behaviors are developed, maintained and potentially changed, gaining knowledge about family dynamics and how to approach familial health promotion is essential. But which methodological approaches are best suited to collecting data for generating such knowledge? We propose using participatory family workshops as a method to generate in-depth data on health-related psychosocial family dynamics, the goal is to improve the field of familial health promotion. We have used family workshops in a variety of settings among various target groups in different research and development projects. In the present article, we re-visit and discuss three research projects focusing on (i) families living with type 2 diabetes, (ii) family-based prevention of childhood obesity and (iii) families with a child with type 1 diabetes. We present experiences with all phases involved in planning and facilitating research workshops. Key points are discussed in relation to implications and perspectives for practice and research. Family workshops are complex and sometimes unpredictable. However, when family workshops are successful, they provide rich and dynamic in-depth data that cannot be produced using more traditional forms of data collection. The article provides an outline of experiences as well as hands-on recommendations for working with family workshops.